Employee Loyalty at Perum Perhutani Divre East Java through Organizational Factors in Human Resource Management Practices: Loyalitas Karyawan di Perum Perhutani Divre Jawa Timur Melalui Faktor Organisasional dalam Praktik Manajemen Sumber Daya Manusia - Hafidz Wahyu Ramadhan; Teguh Soedarto; Mirza Andrian Syah (Jurnal Ilmiah Sosio Agribis, 2026)
This research employs a quantitative approach using purposive sampling techniques involving 50 permanent employees as respondents. The analysis was conducted using the Structural Equation Modeling Partial Least Square (SEM-PLS) method with the assistance of SmartPLS 4. The outer model evaluation indicates that all indicators meet the required validity and reliability criteria (loading factor > 0.7; AVE > 0.5; Cronbach's Alpha and Composite Reliability > 0.7). The structural model assessment also confirms an adequate model fit, as shown by an SRMR value of 0.075, an NFI value of 0.784, and a GoF value of 0.781. The adjusted R² value of 0.749 indicates that work-life balance, benefits, job satisfaction, and workload collectively explain 74.9% of the variance in employee loyalty. The hypothesis testing results show that all four variables have a positive and significant effect on employee loyalty, with job satisfaction as the most dominant factor, followed by benefits, work-life balance, and workload. These findings indicate that integrated human resource management practices, particularly those related to employee satisfaction and welfare, play a strategic role in shaping and maintaining employee loyalty at Perum Perhutani Regional Division of East Java.